The Affordable Care Act's young adult mandate was associated with a reduction in pain prevalence. Issue 11 (November 2021) - Do, Duy; Peele, Morgan
Abstract : Abstract: Pain is a major health problem among U.S. young adults. The passage of the Affordable Care Act's young adult mandate in 2010 allowed individuals to remain on their parents' health insurance until age 26. Although studies have documented the positive effects of this mandate on various health outcomes, less is known about its association with self-reported pain among young adults. Using the 2002 to 2018 National Health Interview Survey (N = 48, 053) and a difference-in-differences approach, we compared the probabilities of reporting pain at 5 sites (low back, joint, neck, headache/migraine, and facial/jaw) and the number of pain sites between mandate eligible (ages 20-25) and ineligible (ages 26-30) adults before and after the mandate. In fully adjusted models, the mandate was associated with a decline of 2 percentage points in the probability of reporting pain at any site (marginal effect, −0.02; 95% confidence interval [CI], −0.05 to −0.002; weighted sample proportion, 0.37) and in the number of pain sites (coefficient, −0.07; 95% CI, −0.11 to −0.01; weighted sample average, 0.62). These results were primarily driven by the association between the mandate and the probability of reporting low back pain (marginal effect, −0.03; 95% CI, −0.05 to −0.01; weighted sample proportion, 0.20). Additional analyses revealed that the mandate was associated with improvements in access to care and reductions in risk factors for pain—including chronic conditions and risky health behaviors. To the extent that the results are generalizable to other health insurance programs, removing financial barriers to medical care may help reduce pain prevalence. Abstract : Supplemental Digital Content is Available in the Text.Health insurance expansion under the Affordable Care Act young adult provision was associated with a reduction in self-reported pain among U.S. young adults.